A novel approach to multi‐objective optimisation of the size and location of an improved hybrid flow controller. Issue 18 (24th July 2022) - Moradi, Behzad; Kargar, Abbas; Derakhshandeh, Sayed Yaser; Niaki, Sayed Ali Nabavi
Abstract: Transient stability is one of the major features of power systems operation which can be also considered an objective function in the flexible AC transmission systems (FACTS) allocation problem. This paper introduces a general multi‐level multi‐objective optimisation framework and its application on optimising the size and location of the improved hybrid flow controller (IHFC). IHFC is a new member of the FACTS family whose ability to control power flow and improve power system stability has been investigated. The optimisation problem considers economic and stability‐based objective functions simultaneously, and the allocation problem is formulated as a non‐linear programming (NLP) problem. The New England 39‐bus system has been used as a case study to demonstrate that the proposed framework can provide efficient and economically viable solutions to the allocation problem.